Nitrogen fertilization on grain yields and dry matter of dual-purpose wheat cultivars (Revista de Ciências Agroveterinárias, 2018)
The dual-purpose wheat is intended to forage production and subsequently grain production. The objective was to evaluate BRS Tarumã and BRS Umbu cultivars for forage mass production and grain yield under nitrogen (N) rates. The experiment was conducted in 2014, in experimental randomized blocks with split plot design, using two cultivars of dual-purpose wheat (BRS Umbu and BRS Tarumã) and four nitrogen rates (0, 30, 60, and 120 kg N ha-1), adding a control (0 kg N ha-1),four replicates, the application was split. There was no interaction between cultivars and nitrogen rates. BRS Umbu cultivar was distinguished by plant height, ear length, number of grains per spike, and grain yield. In the dry mass production, the cultivars did not differ. There was linear and positive response with increasing N rates for all yield components and dry mass of forage. It was concluded that the N rate application up to 120 kg ha-1 provided the highest yield in all analyzed parameters, that in relation to yield components, as well as grain yield to BRS Umbu, stands out in relation to BRS Tarumã.
Keywords: BRS Tarumã; BRS Umbu; forage; income yield